Effects of Smartphone on Physical Activity and Academic Performance of Medical Undergraduates of Islamabad: A cross-sectional Study - Amna Imran; Ayesha Fazal; Seemi Tanvir; Sadia Zafar; Nadia Tariq; Sadaf Tariq (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Smartphones have become an essential part of our life, serving multiple functions like messages, calls and navigation. Smartphone users will increase up to 7.5 billion by 2026. Overuse of smartphones not only causes time wastage and health hazards but also have effects on physical activity and academics. Evaluation of these effects was the need of time, so this study was conducted to assess duration of smartphone usage in undergraduate medical students, and their association with physical activity and academic performance was determined.METHODOLOGY: A cross-sectional survey among 384 undergraduates was conducted from April to August 2019 in Islamabad Medical and Dental College, Islamabad. Convenient sampling technique was done. Structured questionnaire containing socio-demographic information along with a smartphone addiction scale was used. IPAQ long form was also used to determine physical activity among the participants. Academic performance was determined through marks percentage obtained in Annual Professional examination. Data was collected and analyzed by using SPSS 21. Frequencies and percentages were calculated and tests of significance were applied.RESULTS: It was observed that smartphone addiction was more pronounced in male participants 112(64.4%) than in females 109(51.9%). Thus, more male participants were found overweight (16.6%) than females (13.8%). Excessive smartphone usage was found to be significantly associated with physical activity (p-value 0.03). However, excessive smartphone usage had insignificant association with academic performance (p-value=0.250).CONCLUSION: A strong association between excess smartphone usage with reduced physical activity was found. However, smartphone usage had no association with the academic performance of students.